The Influence of International Organizations on the Resolution of the Greek-Turkish Political Conflict - Батрименко, Олег Володимирович; Неліпа, Дмитро Васильович; Ткач, Олег Іванович (Київський національний університет імені Тараса Шевченка, 2024)
The article analyzes the influence of the European Union on the Greek-Turkish international political conflict. The set of scientific studies of Greek-Turkish relations is relevant in several dimensions: attention is focused on the nature of conflict communications, which provides a dimension of relations with the European Economic Community (EU) and the European Union (EU); turning points and periods of positive changes began in the Greco-Turkish conflict. The article is a theoretically grounded review of opinions and approaches about the causes, means, and consequences of EU participation in Greek-Turkish relations. It was determined that there is a lack of research devoted to the analysis of the impact of the EU on the ongoing Greek-Turkish conflict. The notions of Greek-Turkish relations about the role of the EU remain insufficiently theorized, remain analytical bases that consider all possible sources of EU influence, connect them with proitic, economic factors and conditions. It is proved that there is a gap filling. It was found out that, by specifying and alternatively applying the criteria of confusion about crucial turning points, the nature, scale of change can be corrected through defining the complex structure of your EU influence pathways.

У статті аналізується вплив Європейського Союзу на греко-турецький міжнародний політичний конфлікт. Сукупність наукових досліджень греко-турецьких відносин має актуальність в кількох вимірах: акцентується увага на природі конфліктних комунікацій, що забезпечує вимір відносин з Єєвропейським Економічним Співтовариством (ЄЕС) і Європейським союзом (ЄС).; в греко-турецькому конфлікті визначаються переломні моменти та періоди позитивних змін. Стаття є теоретично обґрунтованим оглядом думок та підходів про причини, засоби, наслідки участі ЄС стосовно грецько-турецьких відносин. Встановлено, що існує дефіцит досліджень, які присвячені аналізу впливу ЄС на проітичний греко-турецький конфлікт. Уявлення з греко-турецьких відносин про роль з ЄС залишаються недостатньо теоретизованими, спостерігається відсутність ананалітичної основи, яка розглядає всі можливі джерела впливу ЄС, пов’язує їх з проітичними, економічними факторами та умовами. З’совано, що за допомогою конкретизації та послідовного застосування критеріїв плутанина щодо вирішальних поворотних моментів, щодо характеру, масштабу змін може бути виправлена через визначення комплексної структури потенційних шляхів впливу ЄС.
Вплив міжнародних організацій на розв’язання міжнародного політичного греко-турецького конфлікту
Keywords: politics; democracy; political conflict; national identity; conflict resolution methods; Greek-Turkish relations; international conflict; international relations; інформаційна політика; демократія; політичний конфлікт; національна ідентичність; методи вирішення конфліктів; греко-турецькі відносини; міжнародний конфлікт; міжнародні відносини; етнополітичний конфлікт